Effect of Padina minor powder extract as biostimulant and black soldier fly fertilizer on growth and yield of soybean (Glycine max L. Merrill) - Noli, Zozy Aneloi; Suwirmen, Suwirmen; Julita, Julita (Universitas Padjadjaran, 2023)
Soybean production has not met domestic demand, causing dependence on imported soybeans. Increasing soybean production can be done by giving organic materials such as fertilizer and biostimulants. Applying Padina minor extract as a biostimulant and black soldier fly (BSF) fertilizer can be an alternative to increase the growth and production of soybean. The research aims to determine the effect of Padina minor powder extract, BSF fertilizer, and the combination of Padina minor powder extract and BSF fertilizer on the growth and yield of soybean. This research was carried out from April to July 2021 at the Plant Physiology Laboratory and Greenhouse, Department of Biology, Andalas University, Padang. The experiment was arranged in a Completely Randomized Design with four treatments (control or without extract and fertilizer), Padina minor extract, BSF fertilizer, and the combination of Padina minor extract and BSF fertilizer) and six replications. The results showed that the extract of Padina minor did not significantly affect the growth and yield of soybean. BSF fertilizer significantly increased the number of leaves, branches, leaf area, chlorophyll b, and total chlorophyll of soybean. The combination of Padina minor extract and BSF fertilizer gave similar effects as BSF fertilizer on increasing the number of leaves, leaf area, chlorophyll b, and total chlorophyll of soybean.